Reversion of fruit‐dependent inhibition of flowering in Citrus requires sprouting of buds with epigenetically silenced CcMADS19. Issue 1 (1st September 2021) - Mesejo, Carlos; Marzal, Andrés; Martínez‐Fuentes, Amparo; Reig, Carmina; de Lucas, Miguel; Iglesias, Domingo J.; Primo‐Millo, Eduardo; Blázquez, Miguel A.; Agustí, Manuel
Summary: In Citrus, the response to environmental floral inductive signals is inhibited by the presence of developing fruits. The mechanism involves epigenetic activation of the CcMADS19 locus ( FLC orthologue), encoding a floral repressor. To understand how this epigenetic regulation is reverted to allow flowering in the following season, we have forced precocious sprouting of axillary buds in fruit‐bearing shoots, and examined the competence to floral inductive signals of old and new leaves derived from them. We have found that CcMADS19 is enriched in repressive H3K27me3 marks in young, but not old leaves, revealing that axillary buds retain a silenced version of the floral repressor that is mitotically transmitted to the newly emerging leaves, which are able to induce flowering. Therefore, we propose that flowering in Citrus is necessarily preceded by vegetative sprouting, so that the competence to respond to floral inductive signals is reset in the new leaves.